The mediating role of core self-evaluation in the association between perceived peer relationship quality and loneliness in university students - Hongxiu Tan; Wen Xiao (PLoS ONE, 2025)
This study investigated the mediating role of core self-evaluation (CSE) in the relationship between the perception of peer relationship quality and loneliness among university students during the COVID-19 pandemic. An online survey was conducted with 462 university students (mean age: 20.7 ± 1.56 years; age range: 18 to 25 years) using the Peer Relationships Satisfaction Scale, Core Self-Evaluation Scale, and UCLA Loneliness Scale. The results revealed a significant negative correlation between perceived peer relationship quality and loneliness, as well as between CSE and loneliness. Core self-evaluation accounted for 36.23% of the total effect of peer relationship quality on loneliness. Additionally, female students reported higher levels of loneliness than male students, and students from rural areas experienced greater loneliness than their urban counterparts. The study concluded that fostering high-quality peer relationships and enhancing core self-evaluation could be effective strategies for reducing loneliness among university students.